Predicting cardiorespiratory fitness in female soccer players: the basque female football cohort study - Garcia-Tabar, I.; Iturricastillo, A.; Castellano, J.; Cadore, E. L.; Izquierdo, M.; Setuain, I. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To develop gender-specific operational equations for prediction of cardiorespiratory fitness in female footballers.